Penerapan ANP-TOPSIS untuk Pengukuran Kinerja Human ResourcesProcurement Section - Kaluku, Moh Ramdhan Arif; Jie, Ferry (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
One practice is important in a company's performance is in the process of procurement. Performance of human resources in a company shows a measure of the quality of work and is used as a measure to observe the performance levels of employees in a company. The level of underperformance will have an impact on the quality of jobs that will be performed that could have a serious impact on the company. It is necessary to develop a human resources performance measurement using ANP method and TOPSIS, the procurement section of the company. This study aims to assist in the decision making process and seek alternative solutions to address the issues in order to measure the level of performance of each employee. In this study, the method used to obtain the ANP normal weight that will be used for calculations on TOPSIS method. The input parameters in the weighting process ANP is also very affecting for ranking process to be performed on TOPSIS. The input parameter is the ratio of any existing KPI indicators on procurement section. The results showed that the proposed method can be used to build a predictive performance measurement on procurement human resources section. From the research the highest performance values obtained on procurement section is 0.6936 while the lowest value was 0.3584.Â Â